Fibroblast-stimulating lipopeptide-1 as a potential mucosal adjuvant enhances mucosal and systemic immune responses to enterovirus 71 vaccine. Issue 29 (5th July 2018) - Lin, Yu-Li; Cheng, Pei-Yun; Chin, Chiao-Li; Huang, Li-Min; Lin, Shr-Yu; Chiang, Bor-Luen
Abstract: To prevent viral infection at the site of entry, mucosal vaccines are potent tools for inducing IgA secretion for defense. Because Toll-like receptor (TLR) ligands serve as strong adjuvants, two ligands that mimic the structure of mycoplasmal and bacterial lipopeptides represent interesting vaccine candidates. Pam3CSK4, a synthetic triacylated lipopeptide, interacts with TLR2/1. Because fibroblast-stimulating lipopeptide-1 (FSL-1), a synthetic diacylated lipopeptide, is recognized by TLR2/6, we targeted the potential immuno-inducibility of Pam3CSK4 and FSL-1 as adjuvants of an enterovirus 71 (EV71) mucosal vaccine. Naïve BALB/c mice were used for intranasal immunization three times over a 3-week interval, with results showing that EV71-specific IgG and IgA in serum, nasal washes, bronchoalveolar lavage fluid, and feces from the EV71 + FSL-1 group were significantly higher than levels observed in mice treated with EV71 + Pam3CSK4, EV71 alone, or the control group treated with phosphate-buffered saline. Furthermore, we observed more EV71-specific IgG and IgA-producing cells in treatments using EV71 formulated with FSL-1. Additionally, T cell-proliferative responses and interferon-γ and interleukin-17 secretion were significantly increased when inactivated EV71 was formulated using FSL-1. Moreover, serum from immunized mice was capable of neutralizing the infectivity of EV71 (C2 genotype) and was able to cross-neutralize the B4 and B5 genotypes of EV71. Our data suggested that FSL-1 could be used as an efficient adjuvant for intranasal EV71-vaccine immunization.